Apoyo a la Supervisión de Obra del Proyecto Santorini de la Empresa Módulo Ingeniería y Construcción de Duitama (2021)
The company Módulo Ingeniería y Construcción S.A.S is located in the city of Duitama Boyacá, it carries out engineering, technical consulting and construction activities. The Santorini multifamily is currently being executed, which is made up of 20 residential units and has a constructed area of 1606.52 m²; For the monitoring and control of the work, the construction company requires support in the supervision of the project by the civil engineering intern. This document presents the constructive activities in which the student provided support during the internship, fulfilling the tasks of engineering assistant for the supervision of the work in order to contribute to the optimization of the Módulo Ingeniería y Construcción S.A.S processes, this putting into practice what was learned during academic training.